THE EXTINCT WEKALA OF SULAYMAN PASHA 1525 AD, AS EXAMPLE OF THE ISLAMIC WEKALAS IN ROSETTA - Mohammed Al-Zoheiry (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2019)
The importance of this research is attributed to the restoration of the architectural heritage of Rosetta in the Ottoman era, through transform information into architectural designs of the buildings that existed at those times and were destroyed through various reasons, highlighting the importance of urban and architectural style. In this work, we examined these documents and information about Wekala of Sulayman Pasha and Transformed information into architectural designs to provide the reader and researcher with a picture of these monuments as if they were before. Since these documents are numbered in hundreds and are kept in volumes, we have dealt with them as little as we need in this work, and we resorted to other sources to complete the information that we did not find in the documents mentioned.